PENINGKATAN WAWASAN TENTANG URGENSI PENGELOLAAN SUMBERDAYA PERIKANAN BERKELANJUTAN DI TELUK STARRING PADA SISWA SMA NEGERI 1 MORAMO - Bujang, Azis; Kamri, Syamsul; Mustafa, Ahmad; Tadjuddah, Muslim; Alimina, Naslina; Abdullah, Abdullah; Indrayani, Indrayani (Bina Bahari, 2024)
This community service aims to increase the awareness of SMAN 1 Moramo students about the potential of fisheries in Starring Bay, as well as problems and opportunities for management. Through counseling activities, students are invited to understand the importance of sustainable fisheries management. The results showed an increase in students' understanding of the potential of Starring Bay and problems such as destructive fishing, pollution, and lack of knowledge about conservation. Students also showed enthusiasm in formulating ideas for sustainable fisheries management in the future. This activity is expected to be the first step in cultivating sustainable fisheries resource management among the younger generation.